Analysis Of The Influence Of Brand Image and Patient Experience On the Impact Of Brand Image and Patient Experience On Patient Loyalty With Trust As a Mediating Variable in Private Insurance Inpatients at RS MRCCC Siloam Semanggi - Marselinus Surya; Endang Ruswanti; Wahyuni Dian Purwati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Patient loyalty is an attitude that drives behavior to return to using the services of a hospital, incorporating emotional aspects, particularly making regular and repeated visits with high consistency. This study aims to obtain empirical evidence of the relationship between brand image, patient experience, and trust on the loyalty of inpatients using private insurance at MRCCC Siloam Semanggi Hospital. The background of this research is the trend of decreasing patient numbers in 2023 among those with private payment and non-JKN insurance. Additionally, secondary data from patient feedback forms revealed some patients were dissatisfied with services not meeting their expectations and showed a tendency to switch hospitals. Based on the data, there is a noticeable decline in the number of patients in the inpatient unit, reflecting an issue with patient loyalty towards MRCCC Siloam Hospital. The research design used is a quantitative study with a cross-sectional design, involving 75 inpatients as the subjects of this study. Data collection was carried out by distributing questionnaires to inpatients randomly, with informed consent. The analysis tool used is Structural Equation Modeling (SEM). The results of the study based on the analysis test show a significant influence of brand image, patient experience, and trust on patient loyalty. However, the influence of brand image and patient experience on patient loyalty, when mediated by trust, is not significant. It is recommended that the hospital improve patient loyalty by enhancing the quality of services through various internal evaluations of the existing system to meet patient expectations and build stronger relationships.